2008
DOI: 10.1017/s0142716408080065
|View full text |Cite
|
Sign up to set email alerts
|

Bilingual language representation and cognitive processes in translation

Abstract: Atext-translation task and a recognition task investigated the hypothesis thatsemantic memoryprincipally mediates translation from a bilingual's native first language (L1) to her second language (L2), whereaslexical memorymediates translation from L2 to L1. This has been held for word translation by the revised hierarchical model (RHM) of Kroll and Stewart. The results from Greek, English, and French fluent bilinguals showed semantic errors in L1–L2 direction and lexical errors in L2–L1 direction in the transl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…Considering the fact that there have been very few attempts to examine L2 processing mechanisms using a translation paradigm (see Hatzidaki and Pothos, 2008; Macizo and Bajo, 2004), and that translation has the potential to provide an explicit output representation of L2 speakers’ comprehension, this study used an off-line translation paradigm to specifically address the question of L2 speakers’ integration of different kinds of information. Specifically, if it were to be found that translations sometimes contained accurate reflections of the input language morphosyntactic features, yet inaccuracies in semantic role information, it would be difficult to argue that the semantic errors were due to incomplete morphosyntactic processing of the input language.…”
Section: The Current Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the fact that there have been very few attempts to examine L2 processing mechanisms using a translation paradigm (see Hatzidaki and Pothos, 2008; Macizo and Bajo, 2004), and that translation has the potential to provide an explicit output representation of L2 speakers’ comprehension, this study used an off-line translation paradigm to specifically address the question of L2 speakers’ integration of different kinds of information. Specifically, if it were to be found that translations sometimes contained accurate reflections of the input language morphosyntactic features, yet inaccuracies in semantic role information, it would be difficult to argue that the semantic errors were due to incomplete morphosyntactic processing of the input language.…”
Section: The Current Studymentioning
confidence: 99%
“…Although a considerable body of research has examined how two languages are represented in bilingual memory using single-word translation paradigms (Kroll and Stewart, 1994; Kroll and Tokowicz, 2001), there have not been many studies to examine sentence-level translation; only recently have experimental studies been conducted to explore the processes of sentence-level translation from a psycholinguistic perspective (Hatzidaki and Pothos, 2008; Macizo and Bajo, 2004, 2006). These studies in sentence-level translation explored two conflicting psycholinguistic theories of translation which were proposed decades ago.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, in the psychological literature on translation and studies of bilingual word recognition at large, the unit of study has been single words presented out of context (Talamas, Kroll & Dufour, 1999; see also De Groot & Keijzer, 2000; De Groot & Poot, 1997; Frenck-Mestre & Prince, 1997; but see Hatzidaki & Pothos, 2008; Schwartz & Kroll, 2006). Across numerous studies involving lexical decision or word naming, cognate status and orthographic relatedness of words across languages affects bilingual word recognition, suggesting that, even when the task does not require translation, translation equivalents are activated (e.g., Van Hell & Dijkstra, 2002).…”
mentioning
confidence: 99%
“…Here, we used error analyses of translation data (where learners translated newly-learned vocabulary items into English) to examine the mechanisms that may underlie the effects of bilingualism on vocabulary learning. Translation-like tasks have been frequently used in previous research to delineate the structure of the bilingual lexical system (e.g., Hatzidaki & Pothos, 2008; Kroll & Stewart, 1994, Sunderman & Kroll, 2006) and production error data have been widely utilized to pinpoint the stages in the lexical retrieval process (e.g., Caramazza, 1997; Goldrick, Folk, & Rapp, 2010; Rapp & Goldrick, 2000; Roelofs, 2007). In the present study, we used a translation task where participants translated the newly-learned words into their native language in order to examine the error patterns in bilinguals’ vs. monolinguals’ retrieval data.…”
mentioning
confidence: 99%
“…For example, different patterns of translation vs. picture-naming performance in bilinguals have been used as evidence for the involvement of the semantic system in second-language (L2) processing (e.g., Kroll & Stewart, 1994). Within this line of research, Hatzidaki and Pothos (2008) have demonstrated that bilinguals tended to make semantic (i.e., meaning-related) errors when translating text from the native language (L1) into the L2 and lexical (i.e., form-related) errors when translating text from the L2 into the L1. These findings were interpreted to suggest that the semantic system is more activated by the native language than by the second language during translation tasks.…”
mentioning
confidence: 99%